Striatal miR-183-5p inhibits methamphetamine-induced locomotion by regulating glucocorticoid receptor signaling - Song, Sang-Hoon; Jang, Won-Jun; Jang, Eun Young; Kim, Oc-Hee; Kim, Haesoo; Son, Taekwon; Choi, Dong-Young; Lee, Sooyeun; Jeong, Chul-Ho (Frontiers in Pharmacology, 2022)
MicroRNA (miRNA)-mediated striatal gene regulation may play an important role in methamphetamine (METH) addiction. This study aimed to identify changes in novel miRNAs and their target genes during METH self-administration and investigate their roles in METH-induced locomotion. RNA sequencing analysis revealed that mir-183-5p was upregulated in the striatum of METH self-administered rats, and target gene prediction revealed that the glucocorticoid receptor (GR) gene, Nr3c1, was a potential target gene for mir-183-5p. We confirmed that single and repeated METH administrations increased METH-induced locomotion and plasma corticosterone levels in rats. Additionally, increased miR-185-5p expression and decreased GR gene expression were observed only in the repeated-METH-injection group but not in the single-injection group. We then investigated the effects of miR-183-5p on METH-induced locomotion using a miR-183-5p mimic and inhibitor. Injection of a mir-183-5p mimic in the striatum of rats attenuated METH-induced locomotion, whereas injection of a miR-183-5p inhibitor enhanced the locomotor activity in METH-administered rats. Furthermore, the mir-183-5p mimic reduced the phosphorylation of tyrosine hydroxylase (TH) whereas the inhibitor increased it. Taken together, these results indicate that repeated METH injections increase striatal miR-183-5p expression and regulate METH-induced locomotion by regulating GR expression in rats, thereby suggesting a potential role of miR-183-5p as a novel regulator of behavioral sensitization to METH.